Association of diet quality and physical function among overweight and obese primarily African American older adults with lower extremity osteoarthritis - Schering, Teresa (Nutr Healthy Aging, 2021)
BACKGROUND: Strategies to reduce osteoarthritis (OA) symptoms and increase physical function in persons with lower extremity (LE) OA is a public health priority. OBJECTIVE: To examine associations between diet quality and measures of physical function among overweight and obese older adults with self-reported LE OA. METHODS: 413 overweight and obese primarily African American adults ≥60 years old with LE OA were assessed. Diet quality was quantified using the Healthy Eating Index-2010 (HEI-2010) and Alternative Healthy Eating Index-2010 (AHEI-2010). The six-minute walk, 30-second chair-stands, and timed up-and-go tests were used to assess physical function. Unadjusted and multivariable linear regressions were performed to assess associations between the diet quality and measures of physical function. RESULTS: The mean age of the subjects was 67.8 (SD 5.9) years and mean BMI was 34.8 (SD 5.5) kg/m(2). Adjusting for total calories, AHEI-2010 total score was associated with superior performance on the six-minute walk test. However, the association was attenuated when also controlling for age, gender, BMI, waist circumference, self-reported pain, and physical activity. HEI-2010 was not associated with the physical function measures. CONCLUSION: AHEI-2010 total score was positively associated with walking speed among older overweight and obese primarily AA older adults with LE OA. However, the association weakened when adjusting for subject covariates. The relationship between diet quality and physical function among health disparate populations should be further investigated in larger cohorts and using rigorous experimental study design.